A Small Disc Area Is a Risk Factor for Visual Field Loss Progression in Primary Open-Angle Glaucoma: The Glaucoma Stereo Analysis Study - Yasushi Kitaoka; Masaki Tanito; Yu Yokoyama; Koji Nitta; Maki Katai; Kazuko Omodaka; Toru Nakazawa (Journal of Ophthalmology)
Purpose. The Glaucoma Stereo Analysis Study, a cross-sectional multicenter collaborative study, used a stereo fundus camera (nonmyd WX) to assess various morphological parameters of the optic nerve head (ONH) in glaucoma patients. We compared the associations of each parameter between the visual field loss progression group and no-progression group. Methods. The study included 187 eyes of 187 patients with primary open-angle glaucoma or normal-tension glaucoma. We divided the mean deviation (MD) slope values of all patients into the progression group (<−0.3 dB/year) and no-progression group (≧−0.3 dB/year). ONH morphological parameters were calculated with prototype analysis software. The correlations between glaucomatous visual field progression and patient characteristics or each ONH parameter were analyzed with Spearman’s rank correlation coefficient. Results. The MD slope averages in the progression group and no-progression group were −0.58 ± 0.28 dB/year and 0.05 ± 0.26 dB/year, respectively. Among disc parameters, vertical disc width (diameter), disc area, cup area, and cup volume in the progression group were significantly less than those in the no-progression group. Logistic regression analysis revealed a significant association between the visual field progression and disc area (odds ratio 0.49/mm2 disc area). Conclusion. A smaller disc area may be associated with more rapid glaucomatous visual field progression.